Thermodynamics and structural properties of a confined HP protein determined by Wang-Landau simulation - Busara Pattanasiri (2018)
Understanding protein folding confined by surfaces is important for both biological sciences and the development of nanomaterials. In this work, we study the properties of a confined HP model protein by three different types of surfaces, namely, surfaces that attract: (a) all monomers; (b) only P monomers; and (c) only H monomers. The thermodynamic and structural quantities, such as the specific heat, number of surface contacts, and number of hydrophobic pairs, are obtained by using Wang-Landau sampling. The conformational «transitions», specifically, the debridging process and hydrophobic core formation, can be identified based on an analysis of these quantities. We found that these transitions take place at different temperatures, and the ground state configurations show variations in structural properties when different surface type is used. These scenarios are confirmed by snapshots of typical states of the systems. From our study, we conclude that the thermodynamics of these transitions and the structural changes depend on the combined actions of both the composition of the H monomers and the P monomers in the HP chain and the surface types.